2009
DOI: 10.1002/pat.1385
|View full text |Cite
|
Sign up to set email alerts
|

Composite polymer electrolytes prepared by in situ copolymerization of poly(methyl methacrylate‐acrylonitrile) on the surface of poly(methyl methacrylate)‐coated nano‐TiO2

Abstract: Composite polymer electrolytes (CPE) for lithium ion batteries are reported. Initially, nano-TiO 2 was modified by coating with a layer of poly(methyl methacrylate) (PMMA) by emulsion polymerization. CPE with this modified nano-TiO 2 were then prepared by the in situ copolymerization of poly(methyl methacrylate-acrylonitrile) (P(MMA-AN)). Morphology, thermal, electrochemical, and spectroscopic measurements were used to characterize the electrolytes. The PMMA-coated nano-TiO 2 was well dispersed in the polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Further, it was also reported that nano-TiO 2 in PMMA effectively increases the maximum working voltage of the CPE [84]. Other interesting effects are reported adding TiO 2 to PEO, such as the reduction of the ionic conductivity temperature dependence [75], high discharge rates [76], or the low activation energy for ion transport in the TiO 2 / P(AN-MMA) composite [85].…”
Section: >150mentioning
confidence: 97%
See 1 more Smart Citation
“…Further, it was also reported that nano-TiO 2 in PMMA effectively increases the maximum working voltage of the CPE [84]. Other interesting effects are reported adding TiO 2 to PEO, such as the reduction of the ionic conductivity temperature dependence [75], high discharge rates [76], or the low activation energy for ion transport in the TiO 2 / P(AN-MMA) composite [85].…”
Section: >150mentioning
confidence: 97%
“…TiO 2 particles also contribute to reinforce the electrode interfacial [75,76,81], mechanical [74,75,79,81] and electrochemical [74,84,85] stability, e.g., an electrochemical stable window up to 5.0 V in a 10% TiO 2 /PEO CPE [74] is obtained. Further, it was also reported that nano-TiO 2 in PMMA effectively increases the maximum working voltage of the CPE [84].…”
Section: >150mentioning
confidence: 99%
“…Gel polymer electrolytes (GPEs), wherein a polymer matrix such as poly(methylmethacrylate) (PMMA) [5][6][7], polyacrylonitrile (PAN) [8], poly(vinylidenefluoride) (PVDF) [9][10][11] or poly(vinylidene-fluoride-co-hexafluoropropylene) [P(VDF-HFP)] [12,13] is swollen in a liquid electrolyte becoming plasticized (i.e. a gelled polymer electrolyte), have attracted particular attention because they may provide lighter, safer and cheaper batteries with longer shelf life, leak proof construction and easy fabrication into desired shape and size [14].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in case of nano filled composites (nano particles or fibers with the scale from 1 nm to as large as 100-200 nm), due to the same magnitude between polymer coils and nano fillers, molecular interaction between the polymer and the nano fillers will give polymer composites unusual properties that conventional polymers cannot possess [1][2][3][4][5][6]. With the emerge and development of micro injection molding process, this kind of amazing material is also applied in it for satisfying the special photonic, electrical, thermal and mechanical requirement of some smart functional micro system parts, e.g.…”
Section: Introductionmentioning
confidence: 99%